Sustainability of TQM Implementation Model In The Indonesia’s Oil and Gas Industry: An Assessment of Structural Relations Model Fit - Wakhid Slamet Ciptono; Abdul Razak Ibrahim; Ainin Sulaiman; Sharifah Latifah Syed A. Kadir (Gadjah Mada International Journal of Business, 2011)
This study purposively is to conduct an empirical analysis of the structural relations among  critical factors of quality management practices (QMPs), world-class company practice (WCC), operational excellence practice (OE), and company performance (company non-financial performance or CNFP and company financial performance or CFP) in the oil and gas companies operating in Indonesia. The current study additionally examines the relationships between QMPs and CFP through WCC, OE, and CNFP (as partial mediators) simultaneously. The study uses data from a survey of 140 strategic business units (SBUs) within 49 oil and gas contractor companies in Indonesia.  The findings suggest that all six QMPs have positive and significant indirect relationships on CFP through WCC and CNFP. Only four of six QMPs have positive and significant indirect relationships on CFP through OE and CNFP. Hence, WCC, OE, and CNFP play as partial mediators between  QMPs and CFP. CNFP has a significant influence on CFP. A major implication of this study is that oil and gas managers need to recognize the structural relations model fit by developing all of the research constructs simultaneously associated with a comprehensive TQM practice. Furthermore, the findings will assist oil and gas companies by improving CNFP, which is very critical to TQM, thereby contributing to a better achievement of CFP. The current study uses the Deming’s principles, Hayes and Wheelwright dimensions of world-class company practice, Chevron Texaco’s operational excellence practice, and the dimensions of company financial and non-financial performances.  The paper also provides an insight into the sustainability of TQM implementation model and their effect on company financial performance in oil and gas companies in Indonesia.